2013
DOI: 10.3923/pjbs.2013.1204.1207
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity Test of Bacterial and Fungal Fish Pathogens in Cirrihinus mrigala Infected with EUS Disease

Abstract: The study was conducted for 8 weeks to determine pathogenic effect of different fish pathogens in Cirrihinus mrigal (C. mrigala) which was infected with EUS disease. The pathogenic organisms (bacteria and fungi) collected from the infected part of the disease fish. Isolation and screening of microbes were carried out with the help of a number of biochemical tests. A total of eight bacterial isolates were obtained from the diseased fish. Out of eight, six bacteria viz., Streptococcus grp Q1, Aeromonas hydrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…In this research, we selected Salmonella enterica and Escherichia coli as Gram-negative indicator bacteria and Micrococcus luteus as Gram-positive indicator bacteria to identify the antimicrobial activity of LAB strains. Salmonella enterica is a common pathogenic bacteria to livestock, while the other two bacteria are also undesirable in silage, because their growth and proliferation not only consume nutriments, but may cause disease to animals ( Sharma and Sihag, 2013 ; Chaudhari and Kariyawasam, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this research, we selected Salmonella enterica and Escherichia coli as Gram-negative indicator bacteria and Micrococcus luteus as Gram-positive indicator bacteria to identify the antimicrobial activity of LAB strains. Salmonella enterica is a common pathogenic bacteria to livestock, while the other two bacteria are also undesirable in silage, because their growth and proliferation not only consume nutriments, but may cause disease to animals ( Sharma and Sihag, 2013 ; Chaudhari and Kariyawasam, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The conjugated α helical region of PspA to Vi enhanced protective immune response and provided protection against pneumococcal infection [14]. Antibody elicited by PspA recombinant protein and DNA vaccine proffer humoral response which is different from fragment crystallizable (Fc), (lgG1/lgG22 ratios) and fragment antigen-binding (Fab) epitopes of the induced antibodies [22]. The tissue culture lethal dose 50 (TCLD 50 ) determined by Cormier and Janes showed that zeolite could be used against hepatitis A virus infection [12].…”
Section: Discussionmentioning
confidence: 99%
“…6-The antibacterial activity of essential oil in vitro: It was confirmed by determining basil essential oil on growing bacteria using plates incubated at 24h. for treatments and 48h for control according to Sharma and Sihag (2013).…”
Section: -Microbiological Analysismentioning
confidence: 99%